The Latest Dietary Guidelines Spat: Communication Challenges. Issue 3 (May 2016) - Rowe, Sylvia B.; Alexander, Nick
Abstract : With the release of the eighth Dietary Guidelines for Americans, nutrition communicators may feel overwhelmed by the growing complexity, both in terms of dietary science and politics. In this article, the guidelines and the evolving communication challenges are reviewed, along with obstacles to public understanding of the government's dietary advice and the sometimes-unacknowledged communication successes. Observers' critiques of the policy document emanating from the scientific report are discussed, The article explores some of the unintended consequences encountered in trying to communicate evolving dietary science and evolving dietary guidance. Finally, some bottom-line, simple suggestions are offered for communicating in an environment of increasingly complex political, environmental, and scientific circumstances.